THE CATEGORY OF THE CHILD-READER: AGE CLASSIFICATION AND CONCEPT DIFFERENTIATION - Panko, O. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of age classification and concretization of the child-reader concept. The key ideas that explain the reception-interpretation of the child-reader are presented. The analysis to the concepts the reader as player, the reader as Hero and Heroine, the reader as thinker is given.